A constitutive view on risk communication in organisations managing high-risk processes: Towards a conceptual framework - Marynissen, Hugo (Cranfield University, 2013)
This study presents a conceptual framework for a constitutive view of risk communication in organisations managing high-risk processes. Over the last decades, multiple incidents in these types of organisations indicate that the mere communication of risk information and safety procedures does not necessarily lead to risk aversive attitudes. Therefore, it might suggest that the traditional transfer of information is not fulfilling its aim, namely to keep the organisation safe. This doctoral thesis proposes a form of constitutive communication that involves all organisational members in an open safety dialogue as an alternative to this informational approach of communication. As such, it offers a way of taking into account the interpretive, subjective aspects of communication and shows how they interweave with formal communication structures to create the possibility of ongoing safe operations. An on-shore gas-receiving terminal on the European continent was the subject for two empirical research studies. Based on multiple methods, including qualitative interviews, ethnographic data analysis, repertory grid-based interviews, and social network analysis, this study indicates how a constitutive dialogue that creates a common mindset concerning safe operations among all staff can be installed and supported. Furthermore, it demonstrates how despite the fact that every individual in this organisation has different perceptions of the present risks, constitutive risk communication leads to coordinated safe behaviour. These findings offer new perspectives on the solution-oriented knowledge about the relationship between risk communication and risk savvy in organisations managing high-risk processes. The theoretical background to this phenomenon was supported by a literature review in the field of risk communication and risk perception in organisations managing complex interactive and tightly coupled processes. These findings, together with those of the empirical research projects, were compared with insights in the theoretical fields of High-Reliability Organisations (HRO) and Communication Constitutes Organisations (CCO), and result in a conceptual framework for a constitutive view on risk communication in organisations managing high-risk processes. This research offers a number of theoretical and practical contributions to the field of HROs, the field of CCO research. It not only confirms key insights into these theoretical fields, it is also the first study that links the use of CCO to organisations managing high-risk technologies.